2013
DOI: 10.1007/s00404-013-3015-5
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cytology with a diagnosis of atypical squamous cells, cannot exclude high-grade squamous intraepithelial lesion (ASC-H): a follow-up study with corresponding histology and significance of predicting dysplasia by human papillomavirus (HPV) DNA testing

Abstract: We conclude that cases diagnosed as ASC-H should be followed-up with caution as they are strongly associated with dysplasia of any grade (63.1%), especially high-grade dysplasia (38.8%). Reflex HPV DNA testing is an important predictor of dysplasia with a positive predictive value of 87.2% in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 16 publications
0
23
2
1
Order By: Relevance
“…Despite these, the majority of Pap smears can be assigned into specific categories [4]. ASC-H is an uncommon cytology interpretation with an estimated incidence of 0.27-0.56% [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these, the majority of Pap smears can be assigned into specific categories [4]. ASC-H is an uncommon cytology interpretation with an estimated incidence of 0.27-0.56% [11].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ASC-H is associated with a higher incidence of high-grade histological lesions than ASC-US [2,3,4]. The aim of the present study is to review the cases of ASC-H diagnosed at a single institution and discuss the clinical management in these cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence from several studies over the past few years supports the role of reflex HPV DNA testing in the initial diagnostic approach for patients with ASC-H on cytology, although many of these previous studies included only limited cases with ASC-H and HPV-negative results [12][13][14][20][21][22][23][24]. These previous studies reported NPVs of .90% of HPVnegative results accompanying ASC-H for predicting highgrade CIN lesions (CIN $2), consistent with the NPV of 91.2% obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Both the current ASCCP and Korean guidelines recommend initial colposcopy with biopsy for women with Papanicolaou test (Pap test) results showing ASC-H, regardless of the HPV test results; however, there have been ongoing debates about the clinical significance and utility of the HPV test for the management of ASC-H [12][13][14].…”
Section: Introductionmentioning
confidence: 99%